Magnetic Properties of La3Ga5.5Ta0.5O14 Single Crystals Doped with Sm3+ and Er3+ Ions - Kaczmarek, S. M.; Leniec, G.; Berkowski, M.; Kazan, S.; Acikgoz, M. (Polish Acad Sciences Inst Physics, 2017)
Electron paramagnetic resonance and magnetic susceptibility measurements were performed for two La3Ga5.5Ta0.5O14 single crystals doped with 1.96 at.% of Sm3+ ions and 3.8 at.% of Er3+ ions. Two magnetically inequivalent sites were found to be responsible for the electron paramagnetic resonance spectra of Sm3+ ions. Both sites reveal a low (at least C-2) symmetry with g(x) similar to 0.46, g(y) similar to 0.46 and g(z) similar to 0.52. The symmetry of isolated erbium ions is higher than C-2. From electron paramagnetic resonance and magnetic susceptibility experiments it results that the ground state of Er3+ ions is Gamma(6) or Gamma(7). Below 51 K electronic transitions within Gamma(6) doublets take place. Between 51 and 60 K, Gamma(6) to Gamma(7) transitions dominate, while above 60 K mainly transitions within Gamma(7) doublet are active.
6th Congress and Exhibition on International Advances in Applied Physics and Materials Science (APMAS) -- JUN 01-03, 2016 -- Istanbul, TURKEY
Keywords: Trigonal (La1-Xndx)3ga5sio14 Crystals; Growth; Laser